PERBANDINGAN HASIL BELAJAR SISWA ANTARA MODEL GUIDED INQUIRY DAN DISCOVERY LEARNING - Indah Permatasari; Feriansyah Sesunan; Ismu Wahyudi (Unika Santu Paulus Ruteng, 2018)
Comparison of Learning Outcomes Students between Guided Inquiry and Discovery Learning Models. The purpose of this research is to compare the learning outcomes between the guided inquiry and discovery learning models in the liquid pressure material for students of SMPN 8 Bandar Lampung. The experimental design in the study used the form of Quasi Eksperimental Design with the Nonequivalent Control Group Design. The data analysis techniques of student learning outcomes using N-gain scores and hypothesis testing using Independent Sample T-Test. Sig. value (2-tailed) of 0.002 <0.05. The results of this study indicate that there are differences in the average cognitive learning outcomes for students between guided inquiry and discovery learning models, this is indicated by the difference in the average N-gain value in the experimental class I of 0.71 with the high category and the average N-gain value in the experimental class II of 0.57 in the medium category.